Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts